Effect of Work Nature and Leave Breaks on Job Satisfaction in Employees: Examining through Mathematical Modelling - Dadhwal, Lt. Rohan; Kaur, Rupinder (Journal of Advanced Research in HR and Organizational Management, 2017)
In this study the issue of leaves/ breaks between work days and its effect on mental health and productivity output has been explored from subjective perspective. Loss of productivity is often substantial, especially absenteeism which may be caused by mental health problems due to prolonged workings and ultimately prove towards negative benefits of organizations. Data from this survey analysis proves that when employees are provided with short leaves, it increases job satisfaction and motivation in the employees. Thus based on this study it is proved that successful employment programmesare more effective when provided with small or frequentjob breaks to the employees of an organization.